An analysis of elementary school teachers' causal attributions related to self-identified success and failure - Can, Banu. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2005., 2005)
The main purpose of this study was to analyze elementary school teachers' (grades 1-5) causal attributions about their self-identified areas of success and failure in terms of locus of causality, stability, and controllability. The sample consisted of 231 teachers from 21 elementary schools located in 12 sub-provinces of Istanbul. The participants responded to a self-administered questionnaire composed of open-ended questions concerning areas they considered themselves 'most successful' and 'least successful' in their profession, and the perceived primary causes of these outcomes, followed by Russell's Causal Dimension Scale. Content analysis was carried out for the open-ended questions. T-tests and one-way analysis of variance were performed to investigate the effects of teachers' gender, educational background, amount of teaching experience, and perceived outcome (success vs. failure) on the causal attributions made to explain these outcomes. Broad categories of perceived causes of success and failure were compared in terms of locus of causality, stability, and controllability. The results indicated that causal attributions for success were more internal, stable, and controllable than those for failure, a finding supported by literature on attribution theory. Female teachers made more internal attributions for success than male teachers. And, male teachers attributed their failures to causes they perceived as being more controllable, compared to female teachers. Amount of teaching experience and educational background had no significant effect on the causal attributions made for success and failure. The most frequently reported areas of success and failure were discussed in relation to policy issues and implications, and their perceived causes were discussed in the context of Weiner's attributional model of achievement motivation.|Keywords: attribution theory, causal dimensions, elementary school teachers, success, failure
Keywords: Elementary school teachers -- Turkey.; Attribution (Psychology)